Pelatihan Menghasilkan Uang Secara Online dengan Bisnis Afiliasi untuk Siswa Magang SMK di Kampus Universitas Mahakarya Asia - Kadarsih Kadarsih; Defi Pujianto; Safaruddin Safaruddin (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
This digital era, the internet has opened up new opportunities in the business world, especially through online business models such as affiliate businesses. These businesses allow individuals to promote other people's products or services and earn commissions from any transactions generated through affiliate links. Affiliate businesses offer potential solutions, but not all internship participants have the understanding and/or skills to take advantage of these opportunities. For this reason, Mahakarya Asia University provides practical training on affiliation. This approach combines theoretical understanding and practical experience, ensuring students increase their knowledge and practical skills.The method of implementing this service involves pre-implementation, implementation and evaluation stages. Identification of problems, interviews with internship supervisors, and socialization of material are carried out at the pre-implementation stage. The training was carried out face-to-face involving 25 vocational school students in the Mahakarya Asia University computer laboratory on September 9 2023. Evaluation is carried out to measure students' success in applying the knowledge and skills acquired during training.The training results show that students are able to register and create a Shopee affiliate account, create affiliate video content, and disseminate affiliate links via social media. Evaluation of participants' understanding showed that most students understood the material and were successful in the practicum. Overall, this affiliate business training is expected to provide additional competency and opportunities to earn income online.